Cultural Statistics: Behind The Weaving Designs of T’nalak Tapestry - Arciosa, Ramil M. (Future Science / FSH-PH Publications, 2024)
This research describes the multidisciplinary approach in between culture and mathematics/ science concepts, bounded with the different ethno modelling approaches. Like ethno modelling in math-ethno mathematics and physics-ethno physics The static value of the every IPs crafts man, evolve the statistical geometric patterns like the crystallize and geometric weaving designs, volume, areas and its skeletal designs most particularly in the geometric designs of some T’nalak handloom tapestry. When the artistic mind works, dynamism of neurons particles create a weaving designs and patterns with frequencies of wavelength that pointing in a symmetrical and elliptical rays of designs down to his affective and psychomotor of every T’nalak weavers, that’s include that application of cultural statistics. The cultural statistics based on the image processing analysis based on amplitude, wavelength and string theory in perfections of the unique designs of T’nalak weaving patterns.